Metabotype variation in a field population of tansy plants influences aphid host selection. (17th August 2018) - Clancy, Mary V.; Zytynska, Sharon E.; Moritz, Franco; Witting, Michael; Schmitt‐Kopplin, Philippe; Weisser, Wolfgang W.; Schnitzler, Jörg‐Peter
Abstract: It is well known that plant volatiles influence herbivores in their selection of a host plant; however, less is known about how the nonvolatile metabolome affects herbivore host selection. Metabolic diversity between intraspecific plants can be characterized using non‐targeted mass spectrometry that gives us a snapshot overview of all metabolic processes occurring within a plant at a particular time. Here, we show that non‐targeted metabolomics can be used to reveal links between intraspecific chemical diversity and ecological processes in tansy ( Tanacetum vulgare ). First, we show that tansy plants can be categorized into five subgroups based up on their metabolic profiles, and that these "metabotypes" influenced natural aphid colonization in the field. Second, this grouping was not due to induced metabolomic changes within the plant due to aphid feeding but rather resulted from constitutive differences in chemical diversity between plants. These findings highlight the importance of intraspecific chemical diversity within one plant population and provide the first report of a non‐targeted metabolomic field study in chemical ecology. Abstract : Plants are superb metabolic factories, generating complex metabolomic mixtures. Chemical diversity can vary substantially among individuals of the same species. This work uses non‐targeted metabolomics to reveal links between intraspecific chemical diversity and ecological processes in tansy ( Tanacetum vulgare ). In particular, we demonstrate how the different tansy metabotypes influenced the natural aphid colonization in the field. With this work, we highlight the importance of intraspecific chemical diversity and provide the first report of a non‐targeted metabolomic field study in chemical ecology.